The war begins in Paris : a novel - Wheeler, Theodore (Little, Brown and Company, 2023)
From the author of Kings of Broken Things and In Our Other Lives comes a literary noir about two female war correspondents whose fates intertwine in Europe. Paris, 1938. Two women Mielle, a shy pacifist and shunned Mennonite who struggles to fit in with the elite cohort of foreign correspondents stationed around the city; the other, Jane, a brash, legendary American journalist, who is soon to become a fascist propagandist. When World War II makes landfall in the City of Lights, Mielle falls under Jane's spell, growing ever more intoxicated by her glamour, self-possession, and reckless confidence. But as this recklessness devolves into militarism and an utter lack of humanity, Mielle is seized by a series of visions that show her an inescapable Jane Anderson must die, and Mielle must be the one to kill her. Structured as a series of dispatches filed from around Europe and based on the misadventures of a real journalist-turned-Nazi mouthpiece, The War Begins in Paris is a cat-and-mouse suspense that examines the relentlessness of propaganda, the allure of power, and how far one woman will go for the sake of her morality.